2021
DOI: 10.1111/joa.13522
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of orbit size in toothed whales (Artiodactyla: Odontoceti)

Abstract: For many marine tetrapods, vision is important for finding food and navigating underwater, and eye size has increased to improve the capture of light in dim ocean depths. Odontocete whales, in contrast, rely instead on echolocation for navigation and prey capture. We tested whether the evolution of echolocation has influenced the orbit size, a proxy for eye size, and examined how orbit size evolved over time. We also assessed variation in orbit size amongst whales and tested how body size, diving ability, soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 117 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…No change in orbit size was apparent at the base of Odontoceti, which is reinforced by the results here showing that Xenorophidae bear relatively similar orbit sizes and angles to archaeocetes and some toothed mysticetes. Large orbits in small cetaceans (e.g., Phocoenidae, Cephalorhynchus, and probably Parapontoporia) are likely driven by paedomorphosis [53]. These authors likewise found a similar link between small eyes and murky freshwater habitats, and also highlighted a slight increase in orbit size within the deep-diving Ziphiidae [53].…”
Section: Evolution Of Rostral Proportions In Neocetimentioning
confidence: 79%
See 3 more Smart Citations
“…No change in orbit size was apparent at the base of Odontoceti, which is reinforced by the results here showing that Xenorophidae bear relatively similar orbit sizes and angles to archaeocetes and some toothed mysticetes. Large orbits in small cetaceans (e.g., Phocoenidae, Cephalorhynchus, and probably Parapontoporia) are likely driven by paedomorphosis [53]. These authors likewise found a similar link between small eyes and murky freshwater habitats, and also highlighted a slight increase in orbit size within the deep-diving Ziphiidae [53].…”
Section: Evolution Of Rostral Proportions In Neocetimentioning
confidence: 79%
“…Large orbits in small cetaceans (e.g., Phocoenidae, Cephalorhynchus, and probably Parapontoporia) are likely driven by paedomorphosis [53]. These authors likewise found a similar link between small eyes and murky freshwater habitats, and also highlighted a slight increase in orbit size within the deep-diving Ziphiidae [53].…”
Section: Evolution Of Rostral Proportions In Neocetimentioning
confidence: 79%
See 2 more Smart Citations
“…Herein correlations between neurocranium shape and ecology in Elasmobranchii are restricted to three broad categories (depth, 'water conditions' and latitude), with most other correlations being lost when taking phylogeny into account (Table 1; Table 2; Supplementary Table S4). Whilst the absence of rate differences between modules in the selachimorph neurocranium (Supplementary Table S5; Supplementary Table S6) provides rudimentary evidence of natural selection across the braincase [53][54], this does not match observed patterns of ecological signal, which appear to differ signi cantly between different regions of the braincase (Table 2). As mentioned previously, the orbit and the rostrum were found to be the most variable regions of the neurocranium, which is notable given the hypothesised functional importance of these structures (Table 2; Supplementary Table S7) [32][33][34].…”
Section: Relationships Between Braincase Shape and Other Ecological V...mentioning
confidence: 96%